Is True Robot Autonomy Possible? (A Philosophical Consideration) - Agatonović, Miloš (Napredak, 2024)
The paper aims to demonstrate that autonomy in action requires self-location so that it is possible to construct autonomous systems only if they are capable of self-localization. The paper briefly presents the history of the idea of humanoid robots, and then in the main part it conceptually discusses the question of the possibility of robot autonomy starting from the problem of indexicals. The paper starts from John Perry’s thesis that indexicals are necessary for action, and subsequently, presents Jenann Ismael’s concept of an agent representing an information system in which indexical information, for example in self-location, connects an information model with the environment. The paper points to examples of robots, such as the Figure 01 model, as systems described by Ismael, which are capable of autonomously performing actions as well as of self-locating.
Keywords: robots; autonomous action; indexicals; self-location; Figure 01 robot model